Distinctive patterns of naïve/memory subset distribution and cytokine expression in CD4 T lymphocytes in ZAP‐70 B‐chronic lymphocytic patients. Issue 1 (24th October 2013) - Monserrat, Jorge; Sánchez, Miguel Ángel; de, Raquel; Díaz, David; Mur, Sonia; Reyes, Eduardo; Prieto, Alfredo; de la, Antonio; Martínez‐A, Carlos; Álvarez‐Mon, Melchor
<x xml:space="preserve">Abstract</x> Background ZAP‐70 upregulation in B chronic lymphocytic leukemia (B‐CLL) cells is a recognized marker of poor prognosis in these patients; the biological basis of this differential clinical outcome nonetheless remains unknown. ZAP‐70 overexpression is considered a surrogate marker of a B‐CLL cell subset. To test whether the differential biological characteristics of these patients also include the T helper population, we studied naïve, non‐terminated memory (NTEM), terminated memory (TEM) and central memory (CM) cells, and cytokine expression by CD4 T lymphocytes from ZAP‐70+ and ZAP‐70− B‐CLL patients. Methods Expression of CD3, CD8, CD45RA, CD27, and CD28 antigens and intracytoplasmic cytokine production (IFNγ, IL‐2, IL‐4, IL‐10, and TNFα) were assessed simultaneously by nine‐color flow‐cytometry in peripheral blood lymphocytes from B‐CLL patients. B cell ZAP‐70 expression in B‐CLL cells was also analyzed by flow cytometry. Results Compared to ZAP‐70− B‐CLL patients, ZAP‐70+ B‐CLL patients showed 1) significant reduction in the naïve T helper subset and expansion of NTEM and TEM subsets, 2) a decrease in the percentage of activated CD4 T lymphocytes expressing IFNγ, TNFα, and IL‐2, and 3) an increase in the percentage of CD4 T lymphocytes expressing IL‐4 or IL‐10. Conclusions In conclusion, in early stage B‐CLL patients, ZAP‐70 upregulation is associated with distinct patterns of activation/differentiation stage subset distribution and of cytokine expression in CD4 T lymphocytes. © 2013 International Clinical Cytometry Society